Myopic Misunderstandings? A Reply to Meyer (JMA 35(2), 2022) - de Haas, Tymon; Leppard, Thomas P.; Waagen, Jitte; Wilkinson, Toby (Journal of Mediterranean Archaeology, 2023)
This paper engages with Nathan Meyer’s (2022) paper ‘Finding Sites in Mediterranean Survey’. Building upon longstanding critiques of Mediterranean survey practices, Meyer argues for a re-direction of survey practices. We feel that several of his core arguments reflect an unbalanced view on the role of site and off-site data in Mediterranean surveys, conflating intensive and siteless surveys. Moreover, while these critiques seem to us unnecessarily negative regarding the analytical potential of off-site data, they also reflect an overconfident attitude towards the use of site data for comparative purposes.